Metodologi Tafsir Modern-Kontemporer di Indonesia - Firdausiyah, Umi Wasilatul (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
Abstract: This article aims to look at the discourse on the modern-contemporary interpretation methodology in Indonesia. The exegesis methodology is needed by the commentators to understand deeply the contents of the al-Qur’an according to the interpretation rules. Likewise, in exegesis works in Indonesia, the use of its methodology in this modern period is more advanced than the previous periods, collaborated with the variety of exegetical methods to answer the challenges of the new era. Some methods of interpretation, according to the author, are relevant to develop, especially the thematic method that can be collaborated with other approach and style.